2020
DOI: 10.5194/bg-17-1327-2020
|View full text |Cite
|
Sign up to set email alerts
|

Fe(II) stability in coastal seawater during experiments in Patagonia, Svalbard, and Gran Canaria

Abstract: The speciation of dissolved iron (DFe) in the ocean is widely assumed to consist almost exclusively of Fe(III)-ligand complexes. Yet in most aqueous environments a poorly defined fraction of DFe also exists as Fe(II), the speciation of which is uncertain. Here we deploy flow injection analysis to measure in situ Fe(II) concentrations during a series of mesocosm/microcosm/multistressor experiments in coastal environments in addition to the decay rate of this Fe(II) when moved into the dark. During five mesocosm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 88 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…142 Shaked et al (2020) 129 emphasized that the enhancement of Fe bioavailability due to photoreduction of Fe(III) may be especially important in the Arctic Ocean, because low temperatures retard the reoxidation of Fe(II) to Fe(III). Hopwood et al (2020) 147 measured Fe(II) in surface coastal waters of Patagonia and Svalbard, where a dynamic redox cycle operates, maintaining considerable concentrations of Fe(II) in solution. The results by Hopwood et al 147 suggested that the observed reoxidation delay of Fe(II) to Fe(III) was possibly due to the autochthonous production of marine Fe(II)-binding ligands.…”
Section: The Total Dissolved Fe(iii) Concentration [Fe T ] Is Given Bymentioning
confidence: 99%
“…142 Shaked et al (2020) 129 emphasized that the enhancement of Fe bioavailability due to photoreduction of Fe(III) may be especially important in the Arctic Ocean, because low temperatures retard the reoxidation of Fe(II) to Fe(III). Hopwood et al (2020) 147 measured Fe(II) in surface coastal waters of Patagonia and Svalbard, where a dynamic redox cycle operates, maintaining considerable concentrations of Fe(II) in solution. The results by Hopwood et al 147 suggested that the observed reoxidation delay of Fe(II) to Fe(III) was possibly due to the autochthonous production of marine Fe(II)-binding ligands.…”
Section: The Total Dissolved Fe(iii) Concentration [Fe T ] Is Given Bymentioning
confidence: 99%
“…DFe distribution in surface water at our study area was significantly affected by atmospheric input indicated by the same patterns of DFe with DAl distributions. The distribution of Fe in seawater is controlled by rate of Fe stabilisation (formation of organic binding ligands) and Fe removal processes (Hopwood et al, 2020;Shaked et al, 2020). Marine organism (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Reported Fe concentrations determined by a diffusive gel technique in Reloncaví Fjord in October 2006 were found to be relatively high; 46-530 nM (Ahumada et al, 2011). Similarly, reported dFe concentrations in the adjacent Comau Fjord at higher salinity are generally in the nanomolar range and remain >2 nM even under post-bloom conditions which suggests dFe is not a limiting factor for phytoplankton growth (Hopwood et al, 2020;Sanchez et al, 2019).…”
Section: Local Drivers Of 2015 Bloom Dynamics In Reloncaví Fjordmentioning
confidence: 93%